1999
DOI: 10.1002/(sici)1096-8628(19990521)84:2<167::aid-ajmg14>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Goldenhar anomaly in one of triplets derived from in vitro fertilization

Abstract: Fig. 1. Patient phenotype showing hemifacial microsomia and skin tags on the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…GS has previously been observed in a few children born following ART. Roesch et al [2001] reported one child born following ICSI, and Ferraris et al [1999] and Yovich et al [1985] each reported one child born after IVF, both born in multiple births. In our study three children (Patients 1, 2, and 4) were the product of ART (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…GS has previously been observed in a few children born following ART. Roesch et al [2001] reported one child born following ICSI, and Ferraris et al [1999] and Yovich et al [1985] each reported one child born after IVF, both born in multiple births. In our study three children (Patients 1, 2, and 4) were the product of ART (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the malformation rate in children conceived by IVF‐ET does not differ from that of the general population 9 . Poland anomaly, 10 DiGeorge syndrome 11 and Goldenhar syndrome 12 after in vitro fertilization have been reported. Our patient appears to be the first case of Treacher− Collins syndrome after IVF‐ET.…”
Section: Discussionmentioning
confidence: 99%
“…One twin in the ICSI group had Goldenhar syndrome, a rare disorder; his twin brother was healthy. The cause of Goldenhar syndrome is unclear but the disorder has been previously reported in one ICSI child (Roesch et al 2001) and two IVF children (Yovich et al 1985; Ferraris et al 1999) born after multiple births. Children born after IVF have also been reported to be at increased risk of cerebral palsy (Strömberg et al 2002).…”
Section: Discussionmentioning
confidence: 99%